Ultrasound-Guided Scalp Blocks for an Awake Craniotomy: A Case Report - Samuel Ern Hung, Tsan; Peter Chee Seong, Tan; Chin Hwee, Goh (International Anesthesia Research Society, 2022)
Ultrasound-guided scalp blocks may revolutionize regional anesthesia for neurosurgery. In this report, we demonstrate that ultrasound-guided scalp blocks can be used effectively for a craniotomy. A 48-year-old patient with a brain tumor at the motor cortex was scheduled for an awake craniotomy. Ultrasound-guided scalp blocks targeting the bilateral supraorbital, supratrochlear, zygomaticotemporal, auriculotemporal, greater auricular, lesser occipital, greater occipital, and third occipital nerves were performed. A total of 29mL of levobupivacaine 0.3% was used. No additional local anesthetic agent was given for skull pinning, skin incision, or the craniotomy. Postoperatively, the patient remained pain-free, and she was discharged without complications. (A&A Practice. 2022;16:e01618.)